2023
DOI: 10.1177/00033197231187230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sarcopenia on Coronary Atherosclerotic Burden, Lesion Complexity, and Major Cardiovascular Events in Elderly Patients With Acute Coronary Syndrome: A 1-year Follow-up Study

Abstract: Sarcopenia is accepted as an indicator of subclinical atherosclerosis. However, its effects on clinical coronary atherosclerotic burden and lesion complexity and major adverse cardiovascular events (MACE) in elderly patients with non-ST elevation myocardial infarction (NSTEMI) are unknown. Therefore, we evaluated these possible effects. Coronary artery disease (CAD) burden and complexity were assessed using the Gensini and TAXus and cardiac surgery (SYNTAX) score, respectively. MACE involving nonfatal myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…On the other hand, the presence of sarcopenia is also associated with cardiorespiratory diseases and adversely affects the cardiovascular system, causing endothelial and vascular dysfunction. Erkan et al found that sarcopenia was an independent risk factor for higher major adverse cardiovascular events in elderly patients with NSTEMI, and other studies also showed poor outcomes in this patient profile [56][57][58]. Moreover, a relationship between poor handgrip strength, slowing walking pace, and CAD has been observed [59,60].…”
Section: Sarcopeniamentioning
confidence: 97%
“…On the other hand, the presence of sarcopenia is also associated with cardiorespiratory diseases and adversely affects the cardiovascular system, causing endothelial and vascular dysfunction. Erkan et al found that sarcopenia was an independent risk factor for higher major adverse cardiovascular events in elderly patients with NSTEMI, and other studies also showed poor outcomes in this patient profile [56][57][58]. Moreover, a relationship between poor handgrip strength, slowing walking pace, and CAD has been observed [59,60].…”
Section: Sarcopeniamentioning
confidence: 97%